Antioxidant efficacy of mangosteen (Garcinia mangostana Linn.) peel extracts in sunflower oil during accelerated storage. (1st December 2015) - Chong, Yee Mun; Chang, Sui Kiat; Sia, Winne Chiaw Mei; Yim, Hip Seng
Abstract: This study evaluated the efficacy of mangosteen peel extracts (100 and 200 ppm) in stabilizing sunflower oil tested under accelerated storage (65 °C) for a period of 24 days. BHA and α-tocopherol were used as comparative standards besides the control. Established parameters such as peroxide value (PV), iodine value (IV), p -anisidine value ( p -AnV), total oxidation value (TOTOX), thiobarbituric acid reactive substances (TBARS) and free fatty acid (FFA) content were used to assess the extent of oil deterioration. After 24 days storage at 65 °C, sunflower oil containing 200 ppm extract of mangosteen peel showed significant lower PV and TOTOX compared to BHA and α-tocopherol. TBARS, p -AnV and FFA values of sunflower oil containing 200 ppm of mangosteen peel extract exhibited comparable inhibitory effects with BHA. Mangosteen peel extract at 200 ppm exhibited inhibitory effect against both primary and secondary oxidation up to 24 days under accelerated storage conditions. Thus, it is suggested that mangosteen peel extract may be used as a potential source of natural antioxidants in the application of food industry to suppress lipid oxidation.